To solve the system of equations by substitution, we can substitute one equation into the other equation and solve for the variable.
Substituting the expression for y from the second equation into the first equation, we have:
2x + 1 = x^2 - 2x + 1
Rearranging this equation, we get:
x^2 - 4x = 0
Factoring out an x, we have:
x(x - 4) = 0
This equation is satisfied when x = 0 or x - 4 = 0.
For x = 0, substituting this value back into the second equation, we get:
y = 2(0) + 1 = 1
Therefore, one solution to the system of equations is (0, 1).
For x - 4 = 0, we have:
x = 4
Substituting this value back into the second equation, we get:
y = 2(4) + 1 = 9
Therefore, another solution to the system of equations is (4, 9).
Hence, the system of equations has two solutions: (0, 1) and (4, 9).
solve the system bysubstitution. y=×^2-2×+1 y=2×+1
1 answer